Shaping Confidence Through Body Image: A Study on Adolescent Girls - Yuda Syahputra (IICET (Indonesian Institute for Counseling, Education and Therapy), 2025)
Adolescence is a critical developmental stage characterized by rapid physical, psychological, and social changes that may significantly influence an individual’s self-perception and self-confidence. Among adolescent girls, body image often becomes a central concern due to bodily transformations during puberty and sociocultural pressures related to beauty standards. This study aims to examine the relationship between body image and self-confidence among adolescent students at SMK Mahadhika 1 Jakarta. Employing a quantitative correlational design with a cross-sectional approach, data were collected from 168 students selected through purposive sampling. The instruments used included a validated Body Image Scale and a Self-Confidence Scale. Data were analyzed using descriptive statistics, Pearson correlation, and simple linear regression with the assistance of SPSS. The results indicate that most students demonstrate a moderate to high level of body image, with 39.70% categorized as moderate and 39.70% as high. In terms of self-confidence, 45.58% of students fall within the moderate category, while 41.17% are categorized as high. Regression analysis reveals that body image has a significant positive effect on self-confidence (F = 45.866, p < 0.001), with an Adjusted R² value of 0.410, indicating that body image contributes 41% to the variance in self-confidence. The regression equation (Y = 26.953 + 0.608X) further demonstrates that an increase in positive body image is associated with an increase in self-confidence. These findings confirm that a more positive body image corresponds to higher levels of self-confidence among adolescents. The study highlights the importance of fostering positive body perception within school environments as part of guidance and counseling interventions to enhance students’ psychological well-being. Strengthening adolescents’ acceptance of their physical appearance may serve as an effective strategy to improve their confidence, social interaction, and overall personal development.